Fear of Missing Out In Generation Z at STMIK AKI - Ari Yunus Hendrawan (Jurnal Indonesia Sosial Teknologi, 2022)
Generation Z is the generation that now dominates the population in Indonesia, namely 27.94%, Generation Z Not the same as teenagers of previous generations, teenagers and Generation Z have characteristics: likes instantly, wants a multi-tasking career (doing several activities at one time), seeking a lot of experience, being familiar with sophisticated gadgets, being active on social media, likes online shopping, likes new technology, fears of being outdated, this has a good impact on the development of Generation Z, especially in this Generation is the Decisive generation in the Church to carry out the Vision of the Church reaching out to the World for the Gospel, but also The bad problem experienced by the Generation, namely fear of missing out (FOMO), according to psychology this is due to the low fulfillment of psychological needs in autonomy and relatedness that occur in the livelihoods of Generation Z children, because this research was conducted to find out the Description of Generation Z Conditions fostered at AKI University with 122 students, using a descriptive quantitative method. The measuring instrument used in this study is the Scale adapted from the Fear of Missing Out's Scale by Przybylski which is compiled based on the factors causing fear of missing out. The results of this study showed that of the 122 study subjects, in general as many as 94 people (77%) were at high levels of FoMO and as many as 28 people (23%) were at a low level. It can be concluded that in general FoMO in the research subjects of social media users at AKI University is relatively high because as many as 94 people have a score above 23.